High-weather-resistance first-face high-temperature glaze and preparation method and application thereof
Patent Information
- Application Number
- CN202611307664.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]本发明的目的在于针对现有第一面高温釉料长期直接暴露于外部环境时耐候性能有待提高,以及提高釉料耐蚀性能与钢化短时烧结性能之间不易兼顾的问题,提供一种高耐候性第一面高温釉料及其制备方法和应用
[0018]1、本发明通过在玻璃熔块中引入La、Ce和P组分,并控制La和Ce的总摩尔量与P的摩尔量关系,使玻璃熔块具备形成稀土磷酸盐晶相的组成基础;结合后续钢化热处理,可在釉层中形成独居石型稀土磷酸盐晶相,有利于提高所得第一面釉层的耐候稳定性。
Abstract
Description
Technical Field
[0001] This invention relates to the field of glass glaze technology, and in particular to a high-weather-resistant high-temperature glaze for the first surface, its preparation method, and its application. Background Technology
[0002] High-temperature glazes can be applied to the glass surface through printing, roller coating, etc., and then sintered during subsequent high-temperature treatment to form a glaze layer. They are widely used in architectural glass, appliance glass, and other decorative or functional glass products. For tempered glass with a first-sided glaze, the glaze layer is located on the side of the glass facing the external environment. During use, it is subjected to environmental factors such as sunlight, rain, humidity, temperature changes, and acidic or alkaline media over a long period. Therefore, the glaze layer requires high weather resistance and long-term stability.
[0003] Existing high-temperature glazes typically use silicate or borosilicate glass frit as the main film-forming component, and adjust the softening temperature, sintering performance, and chemical stability of the glass frit by adding components such as ZnO, Bi2O3, Al2O3, and ZrO2. However, while improving the weather resistance of the glaze layer, it is also necessary to consider the softening and sintering performance of the glass frit within the tempering temperature range. Increasing the dosage of some corrosion-resistant components can easily alter the melting state and sintering characteristics of the glass frit, making it difficult to simultaneously achieve both weather resistance and compatibility with the tempering process.
[0004] Furthermore, existing technologies can improve glaze properties by adding corrosion-resistant crystalline materials, but the dispersion and bonding state between the added crystalline particles and the glass phase will affect the final glaze properties. The glass tempering process is characterized by high temperatures and short heat treatment times. Therefore, further improvements are needed to combine the composition design of the glass frit with the tempering heat treatment process to form a stable crystalline phase that improves the weather resistance of the glaze without adding a separate, long-duration crystallization step, while also considering the sintering performance of the glaze and the long-term weather resistance of the first surface. Summary of the Invention
[0005] The purpose of this invention is to address the problem that the weather resistance of existing high-temperature glazes on the first surface needs to be improved when they are directly exposed to the external environment for a long time, and that it is difficult to balance the improvement of the corrosion resistance of the glaze with the short-term sintering performance of the tempering. The invention provides a high-weather-resistant high-temperature glaze on the first surface, its preparation method and application.
[0006] To achieve the above objectives, the first aspect of the present invention provides a high-weather-resistant first-side high-temperature glaze, the high-temperature glaze comprising glass frit and inorganic pigments; based on the total mass of the glass frit, the glass frit is composed of 40-50% SiO2, 8-15% B2O3, 8-15% ZnO, 5-12% Bi2O3, 4-9% Al2O3, 1-5% ZrO2, 0.5-3% Li2O, 1-5% Na2O and K2O combined, 1-5% CaO and MgO combined, 0.8-4% La2O3, 0.2-2% cerium oxide (calculated as Ce2O3), and 0.5-2.5% P2O5, the sum of the mass percentages of each component being 100%; the ratio of the total molar amount of La and Ce to the molar amount of P in the glass frit is 0.85-1.15:1.
[0007] In this invention, SiO2 serves as the glass network-forming component, forming the basic network structure of the glass melt. B2O3 and Bi2O3 are beneficial for adjusting the melting performance of the glass melt and its softening sintering performance within the tempering temperature range. ZnO, Al2O3, and ZrO2 are used to jointly regulate the glass network structure, chemical stability, and glaze properties after high-temperature sintering. Li2O, Na2O, K2O, CaO, and MgO are used to regulate the melting characteristics, viscosity, and thermal properties of the glass melt. La, Ce, and P constitute the compositional basis for the subsequent formation of rare earth phosphate crystal phases. Controlling the total molar amounts of La and Ce and the molar amounts of P to be close to the stoichiometric relationship of rare earth orthophosphates is beneficial for forming crystal phases characterized by rare earth phosphates during subsequent heat treatment.
[0008] Further, based on the total mass of the glass frit, the glass frit preferably comprises 42-48% SiO2, 10-15% B2O3, 9-14% ZnO, 6-11% Bi2O3, 4-8% Al2O3, 2-4.5% ZrO2, 1-2.5% Li2O, 2-5% Na2O and K2O combined, 1.5-4% CaO and MgO combined, 1-3% La2O3, 0.3-1.5% cerium oxide (calculated as Ce2O3), and 0.6-1.8% P2O5, with the sum of the mass percentages of all components being 100%. Further, the ratio of the total molar amount of La and Ce to the molar amount of P in the glass frit is preferably 0.95-1.05:1, and the molar amount of Ce preferably accounts for 10-35% of the total molar amount of La and Ce. By making La the main component of rare earth elements and allowing Ce to participate in a certain proportion, it is beneficial for Ce to be dissolved into the monazite-type rare earth phosphate crystal phase, thus taking into account both the formation of this crystal phase and the functional effects brought by the Ce component.
[0009] In this application, "cerium oxide calculated as Ce₂O₃" refers to the mass percentage of Ce₂O₃ uniformly calculated based on the Ce element content in the glass melt. It is used to uniformly represent the amount of cerium component added to the glass melt and does not imply that all Ce in the glass melt exists in the Ce³⁺ valence state or the Ce₂O₃ phase. The ratio of the total molar amount of La and Ce to the molar amount of P is calculated after converting the molar amounts of the corresponding elements based on their respective contents in the glass melt.
[0010] Further, taking the total mass of glass frit and inorganic pigments in the high-temperature glaze as 100%, the content of glass frit is 70-92%, and the content of inorganic pigments is 8-30%. The inorganic pigments are preferably high-temperature resistant inorganic pigments capable of withstanding glass tempering temperatures and possessing chemical stability in the glass frit; their type can be selected according to the desired color of the resulting glaze layer. The high-temperature glaze may also include an organic carrier, and the mass ratio of the total mass of the glass frit and inorganic pigments to the organic carrier is preferably 70:30-85:15. The organic carrier may include organic resins and organic solvents, and may further include one or more of dispersants, leveling agents, and thixotropic agents depending on the glazing method, as long as the organic carrier used enables the glass frit and inorganic pigments to form a glaze slurry suitable for application to the glass substrate surface, and can substantially complete thermal decomposition or volatilization during subsequent heating. Furthermore, the glass frit has a particle size D50 of 2–6 μm and a D90 of no more than 12 μm, in order to balance the dispersibility, application performance and subsequent sintering performance of the glaze slurry.
[0011] A second aspect of this invention provides a method for preparing the aforementioned high-weather-resistant first-side high-temperature glaze, comprising melting and rapid cooling, pre-nucleation heat treatment, and pulverizing and glaze preparation steps. Specifically, the mixture used to form the glass fused block is melted at 1250–1400°C for 30–120 minutes to fully melt the raw materials and homogenize the resulting glass melt. The homogenized glass melt is then rapidly cooled to solidify the La, Ce, and P components together with the glass melt in the base glass fused block. The rapid cooling method can be water quenching, metal roller cooling, or other methods that enable rapid cooling of the glass melt to form the glass fused block.
[0012] Before fine grinding of the base glass frit, the base glass frit is subjected to pre-nucleation heat treatment at 520-600°C for 20-90 minutes, preferably at 530-580°C for 30-70 minutes, and then cooled to obtain the pre-nucleation glass frit.
[0013] Furthermore, the phosphorus source used to form the glass frit includes at least AlPO4, and the P provided by AlPO4 preferably accounts for 50% to 100% of the total P provided by the phosphorus source, in terms of molar amount of P. Using AlPO4 as at least part of the phosphorus source allows for the simultaneous introduction of Al and P components into the melting system, wherein the Al component is included in the composition range of Al2O3 in the glass frit, and the P component is included in the composition range of P2O5. When the P provided by AlPO4 is less than 100% of the total P, the remaining P can be provided by other phosphorus sources capable of introducing phosphorus components into the glass system under melting conditions.
[0014] After the prenucleation heat treatment is completed, the prenucleated glass frit is pulverized and ground to a D50 of 2-6 μm and a D90 of no more than 12 μm. It is then mixed and dispersed with inorganic pigments and an organic carrier to obtain the high-weather-resistant first-side high-temperature glaze. The mixing and dispersion can be performed using ball milling, sand milling, three-roll milling, high-speed dispersion, or other dispersion methods suitable for glass glaze preparation in the art. The specific method can be selected based on the glaze viscosity, pigment type, and subsequent glazing method.
[0015] A third aspect of this invention provides the application of the aforementioned high-weather-resistant first-side high-temperature glaze in the preparation of tempered glass with a first-side glaze. The glass floc in the high-temperature glaze undergoes a pre-nucleation heat treatment at 520–600°C for 20–90 minutes before being mixed with inorganic pigments; the high-temperature glaze is formulated into a glaze slurry, and the glaze slurry is applied to the first side of a glass substrate by screen printing, roller coating, spraying, or other suitable methods, followed by drying; the glass substrate with the applied glaze slurry is then subjected to tempering heating, causing the glass floc to soften and sinter, and monazite-type rare earth phosphate crystal phases to precipitate in situ from the glass floc during tempering heating; after tempering heating, the glass substrate is tempered and cooled, thereby forming a glaze layer containing the monazite-type rare earth phosphate crystal phases on the first side of the glass substrate.
[0016] Furthermore, the peak temperature of the glaze layer during the tempering heating process is 650–720°C, and the glaze layer remains within this temperature range for 60–300 seconds. By subjecting the pre-nucleated glass frit to the aforementioned short-duration high-temperature process, the formation of monazite-type rare-earth phosphate crystal phases can be promoted simultaneously with the softening and sintering of the glass frit, thereby combining the glaze sintering process and the crystal phase formation process with the glass tempering process. Furthermore, the thickness of the glaze layer formed on the first surface of the glass substrate after tempering is 10–45 μm. The first surface refers to the surface of the obtained first-sided glazed tempered glass that directly faces the external environment in its intended use state.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. This invention introduces La, Ce and P components into the glass melt and controls the relationship between the total molar amount of La and Ce and the molar amount of P, so that the glass melt has the compositional basis for forming rare earth phosphate crystal phases; combined with subsequent tempering heat treatment, monazite-type rare earth phosphate crystal phases can be formed in the glaze layer, which is beneficial to improving the weather resistance stability of the obtained first glaze layer.
[0019] 2. The present invention sets up a pre-nucleation heat treatment before fine grinding of glass frit. By adjusting the thermal history of the glass frit, it can have suitable crystallization conditions in the subsequent tempering heating process with a shorter time. This can combine the softening sintering of glass frit, the formation of rare earth phosphate crystal phase and the glass tempering process, reduce the need for a separate long crystallization treatment process, and facilitate the connection with the existing glazed tempered glass production process.
[0020] 3. This invention, through the combination of glass frit composition, La / Ce / P ratio, pre-nucleation heat treatment and tempering heat process, enables the obtained first-side glaze layer to have good acid resistance, alkali resistance and accelerated weathering performance, and can maintain small color change and high gloss retention after xenon lamp accelerated weathering treatment. It is suitable for tempered glass with first-side glaze layer directly facing the external environment. Detailed Implementation
[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0022] I. Preparation of Raw Materials and Test Samples
[0023] In this embodiment, quartz powder, boric acid or boron oxide, zinc oxide, bismuth oxide, aluminum oxide, zirconium oxide, lithium carbonate, sodium carbonate, potassium carbonate, calcium carbonate, magnesium carbonate, lanthanum oxide, cerium oxide, and a phosphorus source are used as raw materials for the glass frit. The amount of each raw material is calculated based on the content of the corresponding oxides in the fused glass. For boron, phosphorus, and alkali metal components that may be lost through volatilization during the melting process, the corresponding feed compensation amount can be determined based on preliminary experiments.
[0024] In this application, the cerium component is uniformly converted to Ce2O3. "Converted to Ce2O3" means that the content of Ce element in the glass melt is uniformly converted into the mass percentage of Ce2O3, and does not limit the Ce in the glass melt to exist entirely in the Ce³⁺ valence state or in the Ce2O3 phase.
[0025] The phosphorus source must include at least AlPO4. When the phosphorus provided by AlPO4 is insufficient to cover all phosphorus, the remaining phosphorus is supplemented using NH4H2PO4. P introduced from AlPO4 and NH4H2PO4 is calculated as P2O5; Al introduced from AlPO4 is included in the Al2O3 content of the glass melt.
[0026] The inorganic pigments used are cobalt blue spinel-type high-temperature resistant inorganic pigments from the same batch. The organic carrier is prepared by mixing ethyl cellulose and α-terpineol in a mass ratio of 8:92.
[0027] Table 1 Oxide composition of glass frits in the examples
[0028] <![CDATA[SiO2]]> 45.00 45.22 42.11 40.00 50.00 <![CDATA[B2O3]]> 12.00 13.00 14.00 10.00 11.75 ZnO 12.00 11.00 13.00 15.00 8.00 <![CDATA[Bi2O3]]> 9.00 9.00 10.00 12.00 5.00 <![CDATA[Al2O3]]> 6.00 7.00 5.00 8.00 4.00 <![CDATA[ZrO2]]> 3.00 3.50 4.00 4.00 1.00 <![CDATA[Li2O]]> 2.00 1.50 2.00 1.50 3.00 <![CDATA[Na2O+K2O]]> 4.00 3.00 4.00 4.00 5.00 CaO + MgO 3.00 3.00 2.00 4.00 5.00 <![CDATA[La2O3]]> 2.00 2.20 1.80 0.80 3.50 <![CDATA[Calculation of Ce2O3]]>< 0.80 0.40 0.95 0.20 1.75 <![CDATA[P2O5]]> 1.20 1.18 1.14 0.50 2.00 total 100 100 100 100 100 (La+Ce):P molar ratio 1.014:1 0.959:1 1.048:1 0.870:1 1.141:1 Ce as a percentage of the total molar amount of La+Ce 28.4 15.3 34.4 19.9 33.2
[0029] In Example 1, Na₂O and K₂O were 3.0% and 1.0%, respectively, and CaO and MgO were 2.0% and 1.0%, respectively; in Example 2, Na₂O and K₂O were 2.0% and 1.0%, respectively, and CaO and MgO were 2.0% and 1.0%, respectively; in Example 3, Na₂O and K₂O were 3.0% and 1.0%, respectively, and CaO and MgO were 1.5% and 0.5%, respectively; in Example 4, Na₂O and K₂O were 3.0% and 1.0%, respectively, and CaO and MgO were 3.0% and 1.0%, respectively; and in Example 5, Na₂O and K₂O were 3.0% and 2.0%, respectively, and CaO and MgO were 3.0% and 2.0%, respectively.
[0030] Example 1
[0031] The raw materials were weighed and converted according to the oxide composition shown in Example 1 in Table 1. Among them, in terms of the molar amount of P element, 80% of the P provided by AlPO4 is provided by the total phosphorus source, and the remaining 20% of the P is provided by NH4H2PO4.
[0032] After the raw materials are mixed evenly, they are placed in a high-temperature resistant crucible and melted at 1340℃ for 60 minutes to ensure that the raw materials are fully melted and the resulting glass melt is homogenized. After melting, the resulting glass melt is water-quenched at a temperature controlled at 20-30℃ to obtain a basic glass frit.
[0033] After drying the obtained base glass frit, it was subjected to a pre-nucleation heat treatment at 560°C for 50 min before fine grinding; after the heat treatment was completed, it was cooled to obtain the pre-nucleation glass frit.
[0034] The pre-nucleated glass frit was crushed and ball-milled using ethanol as the grinding medium. After grinding, it was dried to obtain a glass frit with a D50 of 4.0 μm and a D90 of 8.0 μm.
[0035] Taking a total mass of 100 parts glass frit and inorganic pigment, 82 parts glass frit and 18 parts cobalt blue spinel-type inorganic pigment were used; the mass ratio of the total mass of glass frit and inorganic pigment to the organic carrier was 80:20. After high-speed dispersion and grinding with a three-roll mill, a uniformly dispersed high-temperature glaze slurry was obtained.
[0036] The obtained high-temperature glaze was applied to the first side of a 6 mm thick soda-lime-silica glass substrate using screen printing and dried at 150°C for 10 min. The dried glass substrate was then placed in a tempering furnace for tempering heating, so that the peak temperature of the glaze layer reached 690°C, and the glaze layer was kept in the temperature range of 650–720°C for 150 s. Subsequently, it was cooled by air cooling to obtain the first side of glazed tempered glass, with a glaze layer thickness of approximately 25 μm.
[0037] Examples 2-5
[0038] The preparation steps of Examples 2 to 5 are basically the same as those of Example 1, except that the glass frit composition is as shown in Table 1 and the preparation and application parameters are as shown in Table 2.
[0039] Table 2. Main preparation and application parameters of Examples 1-5
[0040] <![CDATA[Proportion of P provided by AlPO4 / %]]> 80 70 90 50 100 Melting temperature / ℃ 1340 1320 1360 1250 1400 Melting time / min 60 50 80 30 120 Prenucleation temperature / °C 560 530 580 520 600 Prenucleation time / min 50 30 70 20 90 D50 / μm 4.0 3.5 5.0 2.0 6.0 D90 / μm 8.0 9.0 10.0 6.0 12.0 Glass frit: Inorganic pigments 82:18 80:20 85:15 70:30 92:8 Total amount of glass frit and pigment: organic carrier 80:20 78:22 82:18 70:30 85:15 Peak temperature of glaze layer / °C 690 680 705 650 720 Residence time at 650~720℃ / s 150 120 210 60 300 Glaze thickness / μm 25 20 30 10 45
[0041] In Example 2, 70% of the P was provided by AlPO4, and the remaining 30% was provided by NH4H2PO4; in Example 3, 90% of the P was provided by AlPO4, and the remaining 10% was provided by NH4H2PO4; in Example 4, 50% of the P was provided by AlPO4, and the remaining 50% was provided by NH4H2PO4; in Example 5, all the P was provided by AlPO4.
[0042] Comparative Example 1
[0043] Using the same glass frit composition, raw material system, melting conditions, glass frit particle size, glass frit to inorganic pigment ratio, organic carrier dosage, and glazing and tempering conditions as in Example 1, the difference is that the water-quenched base glass frit is not subjected to a 560°C, 50-minute pre-nucleation heat treatment, but is directly crushed and ground, and then mixed with inorganic pigments and organic carrier to obtain a high-temperature glaze slurry.
[0044] The remaining preparation and testing methods are the same as in Example 1.
[0045] Comparative Example 2
[0046] The same preparation method and process conditions as in Example 1 were used, except that the P2O5 content in the glass melt was adjusted from 1.20% to 1.62%, and the SiO2 content was adjusted from 45.00% to 44.58%, while the contents of the remaining oxides remained unchanged, and the sum of the mass percentages of all components was 100%.
[0047] The ratio of the total molar amount of La and Ce to the molar amount of P in the obtained glass melt is approximately 0.75:1, which is lower than the 0.85 to 1.15:1 specified in this invention.
[0048] The remaining melting, pre-nucleation, grinding, glazing, printing, drying and tempering conditions are the same as in Example 1.
[0049] Comparative Example 3
[0050] The same inorganic pigments, organic carriers, glazing, glazing and tempering conditions as in Example 1 were used, except that La, Ce and P were not added during the glass melting stage, but were added during the glazing stage in the form of pre-prepared monazite-type rare earth phosphate powder.
[0051] All oxides in the glass frit of Example 1, except for La2O3, cerium oxide and P2O5, were normalized to 100% in relative proportion. The base glass frit was prepared under the same melting and quenching conditions as in Example 1, and then heat-treated at 560°C for 50 min. Subsequently, it was ground to a D50 of 4.0 μm and a D90 of 8.0 μm.
[0052] Pre-prepared monazite-type rare earth phosphate powder with the same La to Ce molar ratio as in Example 1 was added according to the elemental equivalents of La, Ce, and P, so that the amount and molar relationship of La, Ce, and P added in the resulting inorganic system were basically consistent with those in Example 1; the content of inorganic pigments and the mass ratio of inorganic components to organic carriers were also the same as in Example 1. The remaining glazing, printing, drying, and tempering conditions were the same as in Example 1.
[0053] Comparative Example 4
[0054] The same preparation method and process conditions as in Example 1 were used, except that: cerium oxide was removed, and the content of La2O3 was adjusted to 2.79%, the content of SiO2 was adjusted to 45.01%, the content of P2O5 was kept at 1.20%, and the other glass frit components remained unchanged, with the sum of the mass percentages of each component being 100%.
[0055] The molar ratio of La to P in the obtained glass melt is approximately 1.01:1.
[0056] The remaining melting, pre-nucleation, grinding, glazing, printing, drying and tempering conditions are the same as in Example 1.
[0057] Test methods
[0058] 1. Acid Resistance: The acid resistance of the first tempered glaze layer was tested according to ASTM C724-91(2026). The glaze was treated with citric acid and hydrochloric acid solutions as specified in the standard, and the surface changes after exposure to acidic media were evaluated according to a scale of 1 to 7 as specified in the standard. A scale of 1 indicates no significant corrosion, and a higher scale indicates a higher degree of corrosion. At least three parallel samples were prepared for each group.
[0059] 2. Alkali resistance: The alkali resistance of the fired glaze was quantitatively tested according to ASTM C1203-25. Test specimens with a size no larger than 90 mm × 90 mm were prepared separately using the same glaze and heat treatment conditions as in the corresponding examples to ensure that the glaze was consistent with the corresponding examples.
[0060] The sample was placed in a 10% alkaline solution as specified in the standard and subjected to near-boiling conditions for 2 hours. The alkali resistance of the glaze was evaluated by the mass loss per unit area before and after the test, expressed in mg / cm². 2 The smaller the mass loss per unit area, the better the alkali resistance of the glaze.
[0061] 3. Xenon Lamp Accelerated Weathering Performance: Accelerated weathering tests were conducted according to the xenon arc lamp equipment operation method specified in ASTM G155-25, using a daylight-type filter system. The irradiance at 340 nm was controlled at 0.35 W / (m²) during the test. 2 Each cycle consisted of 102 min of continuous light exposure and 18 min of water spraying while continuing to expose to light. The blackboard temperature was controlled at 63°C during the light exposure phase, and the total exposure time was 2000 h.
[0062] Each group should have at least three parallel samples. After exposure, observe whether the glaze layer shows cracking, peeling, obvious powdering or other visible damage, and test the color and mirror gloss before and after aging.
[0063] 4. Color Difference: The reflectance color coordinates of the first glaze layer before and after the xenon lamp accelerated weathering test were measured according to ASTM C1650-25, and the overall color difference ΔE*ab before and after aging was calculated according to ASTM D2244-25. All samples were tested under the same conditions, and measurements were taken at no fewer than 5 locations on each sample, with the average value taken.
[0064] The smaller ΔE*ab is, the better the color retention performance of the glaze after accelerated weathering treatment.
[0065] 5. Gloss retention rate: The 45° specular gloss of the glaze before and after the xenon lamp accelerated weathering test was measured according to ASTM C346-26. At least 5 locations were selected for testing on each sample and the average value was taken.
[0066] The gloss retention rate is calculated using the following formula: Gloss retention rate = Specular gloss value after aging / Specular gloss value before aging × 100%.
[0067] A higher gloss retention rate indicates better surface condition retention of the glaze layer after accelerated weathering treatment.
[0068] 6. Phase analysis: X-ray diffraction was used to analyze the phases of the prenucleated glass melt and the tempered glaze layer. Cu Kα rays were used, and the scanning range 2θ was 10° to 80°. The formation of monazite-type rare earth phosphate crystal phase was determined by comparing the changes in diffraction patterns before and after tempering.
[0069] Test Results and Analysis
[0070] Table 3 Performance Test Results
[0071] Example 1 Crystalline phase detected, characteristic peaks obvious 1 1 0.55 0.35 98.6 Example 2 Crystalline phase detected, characteristic peaks obvious 1 1 0.68 0.48 97.8 Example 3 Crystalline phase detected, characteristic peaks obvious 1 1 0.82 0.62 96.9 Example 4 Detected crystal phase 2 2 1.10 0.88 95.1 Example 5 Detected crystal phase 2 2 1.24 1.05 93.8 Comparative Example 1 Crystalline phase detected, characteristic peaks are weak 3 3 2.10 1.62 87.6 Comparative Example 2 The characteristic peaks of the crystalline phase were weak, and other crystalline phases were detected. 4 3 2.65 2.10 83.1 Comparative Example 3 Detected crystal phase 3 2 1.85 1.45 89.3 Comparative Example 4 Crystalline phase detected (no Ce solid solution present) 3 2 1.55 1.28 91.2
[0072] Table 3 shows that the first glaze layers obtained in Examples 1-5 all exhibit good acid resistance, alkali resistance, and accelerated weathering resistance, with Example 1 showing superior overall performance. Example 1 achieved excellent results in the acid resistance test, and the alkali resistance test showed a unit area mass loss of 0.55 mg / cm² for C12O3. 2 After 2000 hours of accelerated weathering treatment under a xenon lamp, the overall color difference ΔE*ab was 0.35, and the gloss retention rate was 98.6%. Examples 2-5 used different glass frit compositions and process conditions, and their alkali resistance mass loss, overall color difference after accelerated weathering, and gloss retention rate were all maintained at a good level, indicating that a first glaze layer with good weather resistance can be obtained under the composition and process conditions covered by the embodiments of the present invention.
[0073] Compared to Example 1, Comparative Example 1, which did not undergo pre-nucleation heat treatment, showed weaker characteristic peaks in its tempered monazite-type rare earth phosphate crystal phase, and its acid resistance, alkali resistance, and accelerated weathering resistance were all reduced. This indicates that pre-nucleation heat treatment has a positive effect on crystal phase formation and glaze properties during the subsequent tempering process. In Comparative Example 2, after the ratio of the total molar amount of La and Ce to the molar amount of P was reduced to approximately 0.75:1, the crystal phase formation state and weathering properties further decreased, indicating that the compositional relationship between La, Ce, and P affects crystal phase formation and glaze properties.
[0074] Comparative Example 3 used pre-prepared monazite-type rare earth phosphate powder directly added during the glaze preparation stage. Although the corresponding crystalline phase could be detected after tempering, its acid resistance, alkali resistance, and accelerated weathering performance were all lower than those of Example 1. This indicates that the technical route of pre-incorporating La, Ce, and P into the glass melt and combining pre-nucleation with tempering heat treatment is more conducive to obtaining a first glaze layer with good weather resistance than directly adding pre-prepared rare earth phosphate powder. In Comparative Example 4, after removing the Ce component, the monazite-type crystalline phase precipitated after tempering was a rare earth phosphate crystalline phase without Ce solid solution. Its overall color difference and gloss retention performance were also lower than those of Example 1. This indicates that the Ce component dissolved into the monazite-type rare earth phosphate crystalline phase and participated in phase formation, which has a positive effect on the overall weather resistance of the obtained glaze layer.
[0075] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A high-weather-resistant high-temperature glaze for the first surface, characterized in that, Including glass frit and inorganic pigments; Based on the total mass of the glass frit, the glass frit is composed of 40-50% SiO2, 8-15% B2O3, 8-15% ZnO, 5-12% Bi2O3, 4-9% Al2O3, 1-5% ZrO2, 0.5-3% Li2O, 1-5% Na2O and K2O combined, 1-5% CaO and MgO combined, 0.8-4% La2O3, 0.2-2% cerium oxide (calculated as Ce2O3), and 0.5-2.5% P2O5, with the sum of the mass percentages of all components being 100%. The ratio of the total molar amount of La and Ce to the molar amount of P in the glass melt is 0.85 to 1.15:
1.
2. The high-weather-resistant first-surface high-temperature glaze according to claim 1, characterized in that, Based on the total mass of the glass frit, the glass frit is composed of 42-48% SiO2, 10-15% B2O3, 9-14% ZnO, 6-11% Bi2O3, 4-8% Al2O3, 2-4.5% ZrO2, 1-2.5% Li2O, 2-5% Na2O and K2O combined, 1.5-4% CaO and MgO combined, 1-3% La2O3, 0.3-1.5% cerium oxide (calculated as Ce2O3), and 0.6-1.8% P2O5, with the sum of the mass percentages of each component being 100%.
3. The high-weather-resistant first-surface high-temperature glaze according to claim 1, characterized in that, The ratio of the total molar amount of La and Ce to the molar amount of P in the glass melt is 0.95 to 1.05:1, and the molar amount of Ce accounts for 10 to 35% of the total molar amount of La and Ce.
4. The high weather resistance first-side high-temperature glaze according to any one of claims 1 to 3, characterized in that, Based on the total mass of glass frit and inorganic pigments in the high-temperature glaze being 100%, the content of glass frit is 70-92%, and the content of inorganic pigments is 8-30%. The high-temperature glaze also includes an organic carrier, and the total mass ratio of the glass frit and inorganic pigments to the organic carrier is 70:30 to 85:
15. The particle size D50 of the glass frit is 2-6 μm, and the D90 is not greater than 12 μm.
5. A method for preparing a high-weather-resistant high-temperature glaze for the first surface as described in any one of claims 1 to 4, characterized in that, Includes the following steps: S1. Melt the mixture used to form the glass melt at 1250-1400°C for 30-120 minutes to homogenize the resulting glass melt, and then rapidly cool the homogenized glass melt to obtain a basic glass melt containing La, Ce and P components. S2. Before fine grinding the base glass frit, the base glass frit is subjected to pre-nucleation heat treatment at 520-600℃ for 20-90 minutes. After heat treatment, it is cooled to obtain the pre-nucleation glass frit. S3. The pre-nucleated glass frit is crushed and ground to a D50 of 2-6 μm and a D90 of no more than 12 μm, and then mixed and dispersed with inorganic pigments and organic carriers to obtain the high weather resistance first surface high temperature glaze.
6. The preparation method according to claim 5, characterized in that, The phosphorus source used to form the glass melt includes at least AlPO4, and the P provided by AlPO4 accounts for 50 to 100% of the total P provided by the phosphorus source in terms of molar amount of P.
7. The preparation method according to claim 5, characterized in that, The pre-nucleation heat treatment temperature in step S2 is 530–580℃, and the pre-nucleation heat treatment time is 30–70 min.
8. The application of the high weather-resistant first-side high-temperature glaze according to any one of claims 1 to 4 in the preparation of first-side glazed tempered glass, characterized in that, The glass frit in the high-temperature glaze undergoes a pre-nucleation heat treatment at 520–600°C for 20–90 minutes before being mixed with inorganic pigments. The applications include: The high-temperature glaze is applied to the first surface of the glass substrate in the form of a glaze slurry and then dried. The glass substrate with the glaze slurry applied is tempered and heated to soften and sinter the glass frit, and to precipitate monazite-type rare earth phosphate crystal phase in situ during the tempering and heating process. The glass substrate, after being heated by tempering, is subjected to tempering and cooling to form a glaze layer containing the monazite-type rare earth phosphate crystal phase on the first surface of the glass substrate. The first surface is the side of the tempered glass with glaze that faces the external environment directly when in use.
9. The application according to claim 8, characterized in that, During the tempering heating process, the peak temperature of the glaze layer is 650-720℃, and the time the glaze layer is in the temperature range of 650-720℃ is 60-300s.
10. The application according to claim 8, characterized in that, The thickness of the glaze layer formed on the first surface of the glass substrate after tempering and heating is 10–45 μm.